TEACHER TALK AND THE PATTERN OF ENGLISH CLASSROOM INTERACTION IN TEACHING ENGLISH - Hustiana Hustiana; Akbar Akbar (Univeristas Islam Negeri (UIN) Alauddin Makassar, 2021)
The aim of this research was to explore the teacher talk and the pattern of interaction that occur during in the teaching - learning process. The researcher applied qualitative study in English Zone, a Course Institute in Makassar. The data sources were a teacher who has got her BA degree in State University of Makassar two years ago. There are four teenager students who participated in the class. The technique of data collecting consists of doing observation by recording audio-lingual data of the process of teaching English. While, technique of data analysis consist of transcribing data from recorded classroom observation into written text, classifying the types of teacher talk that occurred in the class, identifying the patterns of interaction occur during in the teaching – learning process and concluding the finding from all of the collected data. In brief, it could be concluded that the teacher employed ten from eleven categories of teacher talks, there are: there are eleven types of teacher talks namely dealing with feelings, praising and encouraging, joking, using ideas of students, repeating students’ response verbatim, asking question, giving information, correcting without rejection, giving direction, and criticizing the students’ response. While there are four patterns of classroom interaction that were applied in the study are: Interactions among students or student – students interactions that happened during the small group discussion and during in the classroom discussions teachers – whole class interactions that happened during the class discussion and also this pattern happened when the teacher conveyed learning material and gives instructions to the students, Interactions among teacher – group discussion that happened during the small group discussion when the teacher clarifies the students’ difficulties with the task given. Therefore, it was suggested for the teacher to conducted group discuccion that did not occur in class interaction to improve the students motivation and willingness to work together.